Sistema de controle de uma bicicleta movida a energia elétrica - Alves, Paulo Ricardo de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
Numerous problems related to mobility and pollution are found in large cities due to the large fleet of vehicles present in these metropolitan centers, causing numerous accidents and even diseases related to stress and anxiety. In order to reduce this problem a little, the present work aims to develop a control system for electric powered bicycles, through a bibliographical survey, designing the motor drive circuits and the battery charger and implementing the control algorithms. Adding a system to perform battery charging in a hybrid mode, ie connected to the conventional grid or connected to a photovoltaic panel. The voltage in the photovoltaic panel is verified to obtain the parameters for the construction of the buck, it is implemented the algorithms, it is designed and the circuit of drives of the engine and of the loader, it simulates and it is implemented the circuits to realize bench tests. The simulation results were obtained through specific software for this purpose, and the experimental results were obtained through bench tests. All the tests performed presented results consistent with what was expected.
Monografia
Keywords: Bicicleta; Energia elétrica; Fotovoltaica; Carregador; Controle; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA